Macrophage inhibitory cytokine-1 (MIC-1/GDF15): a new marker of all-cause mortality - Wiklund, Fredrik E (2010)
Macrophage inhibitory cytokine-1 (MIC-1/GDF15) is a member of the TGF-b superfamily, previously studied in cancer and inflammation. In addition to regulating body weight, MIC-1/GDF15 may be used to predict mortality and/or disease course in cancer, cardiovascular disease, chronic renal and heart failure, as well as pulmonary embolism. These data suggested that MIC-1/GDF15 may be a marker of all-cause mortality. To determine if serum MIC-1/GDF15 estimation is a predictor of all-cause mortality we examined a cohort of 876 male subjects aged 35 to 80 years, selected from the Swedish Population Registry, and followed them for overall mortality. Serum MIC-1/GDF15 levels were determined for all subjects from samples taken at study entry. A second (independent) cohort of 324 same-sex twins (69% female) from the Swedish Twin Registry was similarly examined. All the twins had telomere length measured and 183 had serum levels of interleukin 6 (IL-6) and C reactive protein (CRP) available. Patients were followed for up to 14 years and had cause specific and all-cause mortality determined. Serum MIC-1/GDF15 levels predicted mortality in the all-male cohort with an adjusted odds ratio of death of 3.38 (95%CI 1.38–8.26). This finding was validated in the twin cohort. Serum MIC-1/GDF15 remained an independent predictor of mortality when further adjusted for telomere length, IL-6 and CRP. Additionally, serum MIC-1/GDF15 levels were directly correlated with survival time independently of genetic background. Serum MIC-1/GDF15 is a novel predictor of all-cause mortality.